2007
DOI: 10.1371/journal.pone.0000690
|View full text |Cite
|
Sign up to set email alerts
|

The Tricarboxylic Acid Cycle, an Ancient Metabolic Network with a Novel Twist

Abstract: The tricarboxylic acid (TCA) cycle is an essential metabolic network in all oxidative organisms and provides precursors for anabolic processes and reducing factors (NADH and FADH2) that drive the generation of energy. Here, we show that this metabolic network is also an integral part of the oxidative defence machinery in living organisms and α-ketoglutarate (KG) is a key participant in the detoxification of reactive oxygen species (ROS). Its utilization as an anti-oxidant can effectively diminish ROS and curta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
213
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(224 citation statements)
references
References 43 publications
3
213
0
2
Order By: Relevance
“…a-Ketoacids quench H 2 O 2 mainly through the reaction of nonenzymatic oxidative decarboxylation [19]. In this reaction, a-ketoglutarate is converted to succinate, which would support the tricarboxylic acid cycle [38]. Thus, a-ketoglutarate can shunt the tricarboxylic acid cycle on inactivation of ketoglutarate dehydrogenase under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…a-Ketoacids quench H 2 O 2 mainly through the reaction of nonenzymatic oxidative decarboxylation [19]. In this reaction, a-ketoglutarate is converted to succinate, which would support the tricarboxylic acid cycle [38]. Thus, a-ketoglutarate can shunt the tricarboxylic acid cycle on inactivation of ketoglutarate dehydrogenase under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is located in the mitochondrial matrix where, by the oxidation of organic C substrates (pyruvate and/or malate), it releases CO 2 and provides reducing factors such as NAD(P)H and FADH 2 , which are primary substrates for the synthesis of ATP in the electron transport chain in mitochondria (Fernie et al, 2004;Mailloux et al, 2007;Sweetlove et al, 2010) (Figure 2). In turn, the TCA cycle provides C skeleton components and precursors for the biosynthesis of secondary metabolites such as terpenes, amino acids, and fatty acids, among others (Plaxton and Podestá, 2006;Sweetlove et al, 2010).…”
Section: Tricarboxylic Acid Cycle In Plantsmentioning
confidence: 99%
“…At the end of the cycle, OAA is regenerated for re-condensation with acetyl CoA, restarting the cycle (Figure 2) (Mailloux et al, 2007;Sweetlove et al, 2010).…”
Section: Tricarboxylic Acid Cycle In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS) are formed in the mitochondria during respiration. It has been shown that a healthy metabolic network plays a key role in the defense against oxidative stress through the production of enzymes and electron acceptors which participate in the detoxification of ROS [109]. Interference in the mitochondrial cycle results in oxidative stress owing to an increase in ROS, which act as second messengers to induce a cell reaction that may eventually lead to cell death.…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 99%